Mindset-Oriented Negotiation Training (MONT): Teaching More Than Skills and Knowledge - Ade, Valentin; Schuster, Carolin; Harinck, Fieke; Trötschel, Roman (Frontiers in Psychology, 2018)
In this conceptual paper, we propose that both skill set development and mindset development would be desirable dimensions of negotiation training. The second dimension has received little attention thus far, but negotiation mindsets, i.e., the psychological orientations by which people approach negotiations, are likely to have a considerable influence on the outcome of negotiations. Referring to empirical and conceptual mindset studies from outside the negotiation field, we argue that developing mindsets can leverage the effectiveness of skills and knowledge, increase learning transfer, and lead to long-term behavioral changes. We introduce an integrative negotiation mindset that comprises three inclinations which complement each other: a collaborative, a curious, and a creative one. We also discuss activities that help people to develop and enhance this mindset both in and out of the classroom. Our general claim is that by moving beyond the activities of conventional negotiation training, which focuses on skills and knowledge, mindset-oriented negotiation training can increase training effectiveness and enable participants to more often reach what we define as sustainable integrative agreements.